1999
DOI: 10.1211/0022357991772565
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Repeated-dose Local Toxicity in the Nasal Cavity of Rabbits after Intranasal Administration of Different Glycols for Formulations Containing Benzodiazepines

Abstract: To furnish a systemic effect after intranasal administration, a formulation must contain the therapeutic dose in no more than 150 μL, the maximum volume that can be applied as a single administration in one nostril in man. The objectives of these studies were to examine the local toxicity of formulations containing benzodiazepines and to document the effects to support clinical trials in man. After stability, pharmacological and pharmacokinetic studies of several benzodiazepine formulations, we studied nasal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Local toxicity of the formulation must also be considered. In general, penetration enhancers have a potential for toxicity, and might be expected to induce local irritation (45). The cost of possible local irritation or toxicity should be weighed against potential benefits.…”
Section: Formulations and Volumesmentioning
confidence: 99%
“…Local toxicity of the formulation must also be considered. In general, penetration enhancers have a potential for toxicity, and might be expected to induce local irritation (45). The cost of possible local irritation or toxicity should be weighed against potential benefits.…”
Section: Formulations and Volumesmentioning
confidence: 99%
“…PEG is an uncharged, hydrophilic, linear polymer that is nonimm unogenic and has a low order of toxicity (Montaguti et al, 1994;Hjortkjaer et al, 1999). PEG is approved by the Food and Drug Administration (FDA) for use in drugs (parenterals, topicals, suppositories, nasal sprays), foods, and cosmetics.…”
Section: Introduction R E Co M Bin a N T A D En O V Ir A L (Ad) Vectomentioning
confidence: 99%
“…More recently, the nasal route has received a great deal of attention as a convenient and reliable route, and it was investigated for the systemic administration of DZ 19−23 . One of the limitations of this method is that a small administration volume is required and applicable; it has been reported that it is not generally possible to administer a drug more than approximately 150 µL per each application; above this volume, the formulation can be drained out into the pharynx and swallowed 20 .…”
Section: Discussionmentioning
confidence: 99%